Course and medium-term outcomes of implant-associated infection caused by leading gram-negative pathogens - Olga S. Tufanova; Svetlana A. Bozhkova; Ekaterina M. Gordina; Vasily A. Artyukh (Гений oртопедии)
Introduction Implant-associated infection (IAI) caused by gram-negative pathogens is characterized by a more severe, recurrent course and higher mortality than the one caused by gram-positive ones. The main reason is growing antibiotic resistance of these pathogens and the complexity of choosing drugs for inpatient and outpatient therapy. Purpose To evaluate the influence of various factors and compare the features of the course of implantassociated infection caused by P. aeruginosa, K. pneumoniae, A. baumannii in patients with positive and poor treatment outcomes Methods A retrospective analysis of the medical records of 172 patients treated at the Department of Purulent Osteology between January 1, 2017 and December 31, 2022 for implant-associated infection caused by P. aeruginosa, K. pneumoniae, A. baumannii was conducted. Based on the results of a telephone survey or examination, patients were divided into 2 groups: positive and poor treatment outcomes by Delphi criteria. The impact of various factors in the anamnesis, laboratory and microbiological analysis, features of surgical intervention, antibacterial therapy and the course of the early postoperative period on the outcomes was analyzed in the IBM SPSS STATISTICS (version 26). Results Among patients with IAI caused by gram-negative bacteria, the rate of poor outcomes was 45 %, with fatality rate of 10 %. During the comparative study, a statistically significant effect on the development of a poor outcome was shown by the postoperative level of serum albumin (p = 0.002), the sensitivity of the isolated isolate to the tested antibacterial drugs (p = 0.011), the isolation of the pathogen from patients’ biomaterial in the postoperative period (p = 0.001), a more frequent need for intravenous administration of albumin and iron (p = 0.003 and p = 0.056, respectively) and the need for repeated surgical intervention in the early postoperative period (p = 0.001). Discussion IAI caused by gram-negative bacteria is characterized by a prolonged recurrent course and high mortality, primarily associated with the overall growing antibiotic resistance of pathogens which requires an individual approach to both surgical treatment and drug therapy, as well as the development of new tactical approaches to therapy. Conclusion The rate of poor outcomes was 45 %. Hypoalbuminemia and antibacterial resistance of isolates of P. aeruginosa, K. pneumoniae, A. baumannii, detection of the pathogens in the postoperative material, as well as the need for surgical reoperation in the early postoperative period, are risk factors for poor outcomes.